Corporate Social Responsibility, Utilitarianism, and the Capabilities Approach - Renouard, Cécile (Journal of business ethics, 2011)
This article explores the possible convergence between the capabilities approach and utilitarianism to specify CSR. It defends the idea that this key issue is related to the anthropological perspective that underpins both theories and demonstrates that a relational conception of individual freedoms and rights present in both traditions gives adequate criteria for CSR toward the company’s stakeholders. I therefore defend “relational capability” as a means of providing a common paradigm, a shared vision of a core component of human development. This could further lead to a set of indicators aimed at assessing corporate social performance as the maximization of the relational capability of people impacted by the activities of companies. In particular, I suggest a way of evaluating the contribution of extractive companies to the communities close to their industrial sites in extremely poor areas, not from the viewpoint of material resources and growth, but from the viewpoint of the quality of the social environment and empowerment.